Sweet Potato Processing Capabilities among Households in Delta Central Agricultural Zone of Delta State, Nigeria - Wilson Anyanwu; Chinyelu Irene Nwokolo; Angela Izukanne Emodi (Journal of Agricultural Extension)
The study examined the sweet potato processing capabilities among households in the Delta central agricultural zone in Delta State, Nigeria. A multistage sampling procedure was used to select 120 households for the study. Data were collected through a structured questionnaire and analyzed using percentages. Results show that the majority of the households were capable of: sorting sweet potato based on size, shape, and quality (94.2%), peeling of sweet potato using hands and knives (94.2%), and processing sweet potatoes into confectionaries (94.2%). However, the households had low capabilities in the processing of sweet potatoes into starch (34.2%), peeling sweet potatoes using machines (18.3%), and processing sweet potatoes into sparri (15%). The major factors limiting the sweet potato processing capabilities of households were: poor monitoring of government structural programmes (65%), inadequate access to market chain (59.2%), poor sensitization of farmers on the appropriate methods of processing sweet potato (58.3%). The study concluded that households had low capabilities on some sweet potato processing techniques and recommended that stakeholders in the sweet potato value chain should empower households, especially youths on sweet potato value additions and machineries used in sweet potato processing while linking them with available markets to sell their processed products.